Medical degradable metal zinc alloy, manufacturing method and application

Through binder jet additive manufacturing technology, the problem of difficulty in preparing complex degradable zinc alloys is solved in traditional methods, and the low-cost and rapid preparation of zinc alloys with porous structures is achieved. It is suitable for orthopedics and vascular stent implants, and has the ability to personalize customization.

CN120362512AActive Publication Date: 2025-07-25UNIV OF SCI & TECH BEIJING
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510470735.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-15
Publication Date
2025-07-25
Estimated Expiration
2045-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently prepare degradable zinc alloy implants with different shapes and complex structures. The traditional methods are complex in processes and high in cost, and laser powder bed melting equipment is expensive, which limits mass production.

Method used

Using binder jet additive manufacturing technology, a degradable zinc alloy with a porous structure is prepared by laying zinc-based alloy powder on the printing platform and selectively spraying the adhesive, curing the model cross-section, combining vacuum oven curing and degreasing sintering.

Benefits of technology

It realizes the low-cost and rapid preparation of complex shapes of degradable zinc alloys, has good biocompatibility and moderate degradation rate, is suitable for orthopedics and vascular stent implants, and has personalized customization capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120362512A_ABST
    Figure CN120362512A_ABST
Patent Text Reader

Abstract

The invention relates to a medical degradable metal zinc alloy, and a manufacturing method and application thereof. The manufacturing method comprises the following steps: selecting a zinc-based alloy powder material and a binder; laying a layer of the powder material on a substrate of a printing platform, and selectively spraying the binder on the surface of a powder layer formed by the powder material according to the constructed model so as to solidify the section pattern of the constructed model; then the printing platform descends by the thickness of one powder layer, then a layer of powder material is laid, and the process is repeated until the constructed model is printed; after printing is completed, the whole base plate bearing the printing model is taken down and put into a vacuum oven, heat preservation is conducted for a certain time so as to strengthen the curing strength of the binder, redundant powder is removed after curing is completed, and a green body is obtained; and the green body is degreased and sintered, and the medical degradable metal zinc alloy is obtained. The medical degradable metal zinc alloy prepared by binder spraying additive manufacturing has certain mechanical properties, also has proper degradation rate and good biocompatibility, and is expected to be further applied to clinical orthopedics and intravascular stent implantation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additive manufacturing, and particularly relates to a medical degradable zinc alloy, a manufacturing method and an application thereof. Background Art

[0002] Compared with traditional manufacturing methods, additive manufacturing technology is based on the concept of discrete accumulation forming, and is a "bottom-up" material accumulation method, which is widely used in fields such as aerospace, military, automotive industry, and medical. Binder jetting (BJ) is a kind of metal additive manufacturing technology. The specific process includes laying a powder bed, selectively jetting a binder in the powder bed to form bonds between powder particles, and the rest remains loose. The above steps are carried out layer by layer. After printing, it is put into an oven for curing. After completion, a complete green body can be taken out, and finally an appropriate post-treatment method can be selected to obtain the required parts. The binder jetting technology can realize the personalized and rapid prototyping of products, and even mass-produce end parts.

[0003] Zinc (Zn) is an essential trace element for the human body and plays an important role in the synthesis of enzymes and proteins and cell signal transduction. Due to its good biocompatibility and appropriate degradation rate, zinc is expected to become a new generation of biodegradable metal materials for medical use. The preparation process of traditional biodegradable metal implants requires processing methods such as melting, casting, rolling, extrusion or drawing, and then a series of complex procedures such as turning, milling, planing, grinding and welding. It is difficult to produce geometric structures with higher fineness and complexity. Therefore, the process of preparing zinc alloys by traditional processes is relatively complex, not easy to control, and has a high cost. The rapid development of additive manufacturing technology provides a more direct and effective means for the preparation of fine and complex biodegradable metal geometric structures. Laser powder bed fusion (L-PBF) is an additive manufacturing technology suitable for preparing biodegradable zinc alloys. Although it can prepare personalized parts with excellent mechanical properties and complex microstructures, its expensive equipment and strict working environment limit its ability to produce parts quickly and in large quantities.

[0004] A method for preparing a zinc alloy with high plasticity at room temperature is disclosed in the prior art one (CN110205505A). The method is carried out according to the following steps: First, ingredients are prepared according to the weight percentages of the components of the zinc alloy (weight percentage wt.%: manganese 0.1-2, aluminum 0-1, tin 0-2, and the rest is zinc), heated and melted by an electric resistance furnace, and the zinc alloy melt is poured into a water-cooled iron mold; then the zinc alloy casting blank is heat-treated and turned into a disc shape; finally, high-pressure torsion is carried out on the disc-shaped zinc alloy. The method steps of this scheme are cumbersome and difficult to meet the requirements of customized medical implant devices. Summary of the Invention

[0005] To overcome the above problems existing in the prior art, the present invention provides a medical degradable zinc-based alloy, a manufacturing method and an application thereof to solve the above problems existing in the prior art.

[0006] A manufacturing method of a medical degradable zinc-based alloy, the method comprising the following steps:

[0007] S1. After drying the zinc-based alloy powder material, place it in a powder spreading device, and select a binder corresponding to the powder material;

[0008] S2: Lay a layer of the powder material on the substrate of the printing platform. According to the constructed model, selectively spray the binder on the surface of the powder layer formed by the powder material to cure the cross-sectional pattern of the constructed model; then the printing platform descends by the thickness of a powder layer, and then lay another layer of powder material, and repeat the above process until the constructed model is printed;

[0009] S3. After printing, remove the entire substrate carrying the printed model and put it into a vacuum oven, keep it warm for a certain time to strengthen the curing strength of the binder. After curing, remove the excess powder to obtain a green body;

[0010] S4. Degrease and sinter the green body to obtain a sintered part of the medical degradable zinc-based alloy.

[0011] In the above aspects and any possible implementation manners, a further implementation manner is provided, wherein the particle size of the zinc-based alloy powder material is 5 - 50 μm.

[0012] In the above aspects and any possible implementation manners, a further implementation manner is provided, wherein the drying temperature in step S1 is: 60 - 100 °C, and the time is 8 - 12 h.

[0013] In the above aspects and any possible implementation manners, a further implementation manner is provided, wherein the number of powder layers laid is multiple, the thickness of each layer is 30 - 50 μm, the powder spreading speed is 30 - 60 pps, the saturation of the binder sprayed by the piezoelectric nozzle is 60 - 90%, the printing speed of the nozzle in the X-axis is 300 - 500 pps, and the printing speed in the Y-axis is 50 - 150 pps.

[0014] In the above aspects and any possible implementation manners, a further implementation manner is provided, wherein in S3, a vacuum oven is used for curing, the curing temperature is 150 - 250 °C, and the heat preservation time is 120 - 300 min.

[0015] For the aspects and any possible implementation manners described above, a further implementation manner is provided. In S4, the temperature for degreasing is 200 - 350 °C, the heat preservation time is 60 - 300 min, and the heating rate is 2 - 5 °C / min.

[0016] For the aspects and any possible implementation manners described above, a further implementation manner is provided. In S4, the temperature for sintering is 420 - 480 °C, the heat preservation time is 240 - 500 min, and the heating rate is 1 - 3 °C / min.

[0017] The present invention also provides a medical degradable metal zinc alloy, which is manufactured by the method described above. Its surface is a controllable hierarchical porous structure or a dense structure, the compressive strength is 22 - 145 MPa, the hardness is 12 - 84 HV, and the in vitro degradation rate at 28 d is 0.11 - 0.73 mm / year.

[0018] The present invention also provides an application of the medical degradable metal zinc alloy described above in clinical medical implant devices.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses binder jet additive manufacturing to prepare a medical degradable metal zinc alloy. Compared with traditional preparation processes, the present invention is not restricted and can prepare porous parts with various shapes and complex structures. At the same time, compared with other laser and electron beam additive manufacturing technologies, the binder jet additive manufacturing used in the present invention has lower costs and faster preparation speeds. Different from additive manufacturing technologies such as laser powder bed melting, the forming process of the binder jet additive manufacturing in the present invention is carried out at room temperature and in the atmosphere, avoiding problems related to oxidation, residual stress, element segregation, and phase transformation. The loose powder in the powder bed can be highly recycled. In addition, binder jet additive manufacturing does not require the use of an expensive sealed chamber for vacuum or inerting. Therefore, compared with other additive manufacturing technologies, the build volume of the binder jet equipment is the largest (up to 2200×1200×600 mm).

[0021] (2) The medical degradable metal zinc alloy prepared by binder jet additive manufacturing in the present invention has certain mechanical properties and meets the basic mechanical property requirements of trabecular bone and vascular stents. Moreover, the degradation rate of the binder jet zinc alloy is faster than that of other processes. While matching the bone healing and repair rate, it also has good biocompatibility.

[0022] (3) The medical degradable zinc alloy prepared by the present invention can obtain parts with bimodal pores by controlling the binder jet additive manufacturing printing process and sintering process. This is similar to powder metallurgy, that is, designed pores (microchannels) are left after sintering the original blank and pores generated by the process itself (pores within the microstructure). These pores have microchannels and microstructure pores, which can regulate the degradation rate and contribute to bone adhesion and cell ingrowth.

[0023] (4) In the face of the complexity of the geometry of clinical orthopedic and vascular stents, binder jet additive manufacturing can use software such as CATIA, CAD, and SOLIDWORKS to construct models of various complex geometric degradable implants (bone nails, bone plates, etc.) and set corresponding printing parameters for printing to achieve personalized customization of implants. The degradable zinc alloy prepared by the additive manufacturing method provided by the present invention has excellent mechanical properties, a moderate degradation rate, and good biocompatibility, and can be used for medical implant devices including vascular stents, vascular anastomosis devices, bone nails, bone plates, bone filling materials, etc. Description of the Drawings

[0024] Figure 1 Schematic diagram of pure zinc powder used in Example 1;

[0025] Figure 2 Schematic diagram of the microstructure and element analysis of the binder jet additive manufacturing pure zinc specimen in Example 1;

[0026] Figure 3 Schematic diagram of the stress-strain curve of the binder jet additive manufacturing pure zinc specimen in Example 1;

[0027] Figure 4 Schematic diagram of the weight loss and degradation rate of the binder jet additive manufacturing pure zinc specimen at different times in Example 1;

[0028] Figure 5 Schematic diagram of the biocompatibility of MC3T3 cells of the binder jet additive manufacturing pure zinc specimen in Example 1;

[0029] Figure 6 Photograph of the live / dead staining of MC3T3 cells of the binder jet additive manufacturing pure zinc specimen in Example 1;

[0030] Figure 7 Flowchart of the method of the present invention. Detailed Embodiments

[0031] To better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the following detailed embodiments, and similar technologies and methods should be regarded as within the scope of protection of the present invention. To make the technical problems, technical solutions, and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the drawings and specific embodiments.

[0032] It should be clear that the embodiments described in the present invention are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the protection scope of the present invention.

[0033] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms of "a", "the" and "said" used in the embodiments of the present invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0034] As Figure 7 shown, the present invention provides a manufacturing method of a medical degradable zinc-based alloy, and the method includes the following steps:

[0035] S1: Prepare raw materials, take the zinc-based alloy powder material prepared by gas atomization powder making, dry it in a vacuum drying oven and then place it in a powder spreading device. Select an appropriate water-based binder according to the powder material;

[0036] S2: Print the model, lay a layer of the powder material on the substrate of the printing platform, and then the nozzle selectively sprays the binder on the surface of the powder layer according to the model slices to solidify the cross-sectional pattern of the model. Then the platform descends by the thickness of a powder layer, and a new powder layer is laid again. The nozzle repeats the above process until the model printing is completed. The entire printing process can be carried out at room temperature and in air without the protection of an inert chamber;

[0037] S3: High-temperature curing, after printing is completed, immediately remove the substrate carrying the printing powder bed and put it into a vacuum oven, keep it warm for a certain time to strengthen the curing strength of the binder, and remove the excess powder after curing to obtain a green body.

[0038] S4: Debinding and sintering, the debinding process is integrated into the front stage of sintering. By heating in segments or keeping warm for debinding, the volatile molecules in the binder are removed. After this process ends, immediately enter the heating stage and start high-temperature sintering to obtain a dense final part.

[0039] Preferably, the particle size range of the zinc-based alloy powder material is 5 - 50 μm, and the powder at this particle size has better fluidity when spreading powder in the powder spreading device of a binder jet printer.

[0040] Preferably, the drying conditions are: 60 - 100 °C, the time is 8 - 12 h, and the oxygen content of the powder is less than 100 ppm. Under these drying conditions, the powder has low adhesiveness and good fluidity, which is more conducive to the powder spreading process.

[0041] Preferably, the powder spreading roller rotates during the powder spreading process. During the printing process, when the powder spreading roller stops rotating, the powder diffusion is significantly uneven because the powder adheres to the static roller during the spreading process. Compacting the powder with the powder spreading roller plays an important role in increasing the green density.

[0042] Preferably, the number of layers of the laid powder is multiple, the thickness of each layer is 30 - 50 μm, the powder spreading speed is 30 - 60 pps, the saturation of the binder ejected by the piezoelectric nozzle is 60 - 90%, the printing speed of the nozzle in the X-axis is 300 - 500 pps, and the printing speed in the Y-axis is 50 - 150 pps. By using such layer thickness and powder spreading speed, as well as the corresponding binder saturation and printing speed, a green body with dimensions more in line with the design, lower surface roughness, and higher density can be obtained.

[0043] Preferably, the curing temperature of the vacuum oven is 150 - 250 °C, and the heat preservation time is 120 - 300 min. At this temperature and heat preservation time, the strength of the green body is better, which is beneficial for subsequent experiments.

[0044] Preferably, the debinding temperature is 200 - 350 °C, the heat preservation time is 60 - 300 min, and the heating rate is 2 - 5 °C / min. At this temperature and heat preservation time, the debinding residue is less.

[0045] Preferably, the sintering temperature is 420 - 480 °C, the heat preservation time is 240 - 500 min, and the heating rate is 1 - 3 °C / min. The sample obtained at this temperature and heat preservation time is more dense and has higher mechanical properties.

[0046] In the preparation method provided by the present invention, an aqueous binder is used, which fills the gaps between the powder materials and provides temporary bonding during the printing process, ensuring the structural integrity of the green body and finally being removed in the subsequent process, with a residue amount less than 3%.

[0047] The preparation method provided by the present invention has lower cost and faster preparation speed compared with other laser and electron beam additive manufacturing technologies. For example, when printing a plate of zinc alloy parts with the same size of 120 mm × 120 mm × 10 mm, laser powder bed fusion requires the protection of an inert chamber and the printing time exceeds 8 h, while binder jet additive manufacturing can be carried out in the air. At the same time, the nozzle moving speed is faster, and there is no need for preheating the substrate and the air exchange process, and it only takes about 2 - 3 h to complete the printing.

[0048] Due to the support of the loose powder in the powder bed, the preparation method provided by the present invention can construct a corresponding three-dimensional model according to the shape requirements of the actual medical implant, and set corresponding process parameters such as binder saturation and printing speed for printing. It has the characteristics of precise manufacturing and personalized customization, can obtain devices of any shape, and realizes the personalized customization of implants.

[0049] In the sintering process described in step S4, the sintering temperature exceeds the melting point of zinc. Theoretically, when the liquid phase volume is too high, the liquid phase expands out from the surface, resulting in sample deformation and not maintaining its original appearance. However, due to the residue of the binder component and the restraint of the oxide film, the liquid phase will not expand outwards, enabling the sample to still maintain high dimensional accuracy and its shape during liquid phase migration.

[0050] After mechanical property testing, the compressive strength of the zinc-based alloy prepared by the present invention is 22 - 145 Mpa, and the hardness is 12 - 84 HV. In the simulated body fluid degradation test, the degradation rate of the zinc-based alloy is moderate and has a significant increase. The degradation rate in 28 days is 0.11 - 0.73 mm / year, which better matches the requirements of bone implants and vascular implants for the material degradation rate. While the degradation rate of the existing zinc-based alloy prepared by laser powder bed fusion printing in 28 days is only 0.04 - 0.15 mm / year. According to the ISO 10993 standard, after diluting the leaching solution of the zinc-based alloy of the present invention by 10 times, the biocompatibility evaluation shows that when MC3T3 cells are cultured for 3 - 5 days, the cell viability is greater than 90%. The live-dead staining results show that the cells present spindle-shaped and filamentous pseudopodia, and the cell state is good, indicating that the zinc alloy described in the present invention has good biocompatibility.

[0051] The preparation method provided by the present invention can obtain a controllable hierarchical porous structure or a dense block on the surface of the zinc-based alloy by controlling one or several conditions such as the binder saturation, printing speed, sintering temperature and time. The pores in this hierarchical structure are beneficial to cell adhesion and growth, and improve the biocompatibility of the zinc-based alloy prepared by binder jet printing.

[0052] As an embodiment disclosed by the present invention, the present invention also discloses the application of a medical degradable metal zinc alloy in clinical medical implant devices. The clinical medical implant devices include vascular stents, vascular anastomosis devices, bone nails, bone plates, bone filling materials, etc. Since the zinc-based alloy specimen has certain mechanical properties, a moderate degradation rate, and good biocompatibility, it can be used for medical implant devices.

[0053] The following is illustrated by taking examples and comparative examples.

[0054] Example 1

[0055] (1) Take about 3 kg of pure zinc powder with a particle size of 5 - 30 μm and put it into a vacuum drying oven. The drying temperature is set at 80 °C and the time is 10 h;

[0056] (2) Use Magics software to construct the printing model, import it into the operating software of the binder jet printer, and set the printing process parameters, including a layer thickness of 40 μm, a powder spreading speed of 50 pps, an X-axis printing speed of 350 pps, a Y-axis printing speed of 110 pps, and a binder saturation of 80%.

[0057] (3) After printing, place the entire substrate in a vacuum drying oven for curing, set the temperature to 180 °C, and the time to 180 min. After curing is completed, wait until it cools to room temperature and then take it out for powder cleaning to obtain a pure zinc green body.

[0058] (4) Place the green body in a crucible for debinding and sintering. Heat from room temperature to 200 °C and hold for 30 min, then heat to 380 °C and hold for 120 min; then heat to the sintering temperature of 450 °C and hold for 360 min; finally, cool in the furnace to below 100 °C and take it out to obtain a sintered sample of pure zinc. Observe its microstructure, as Figure 2 shown, sintering necks are formed between some powder particles, and its density is statistically analyzed by ImageJ software, indicating that its structure is dense.

[0059] (5) According to the requirements of the national standard GB / T 7314-2017 "Metallic materials - Compression testing at ambient temperature", after cleaning the sintered compression sample with alcohol and deionized water, verify its strength according to the research. The verified compression performance (stress-strain curve) is as Figure 3 shown. At the same time, according to the requirements of GB / T 4340.1-2009 "Metallic materials - Vickers hardness test - Part 1: Test method", verify the hardness of the polished sample. The verified strength results are shown in Table 1.

[0060] (6) Conduct an in vitro immersion test on the pure zinc sample using simulated body fluid, Figure 4 and the results show that the degradation rate of the sample in 28 days is 0.67 mm / year, meeting the requirements of bone implants and vascular implants for the material degradation rate.

[0061] (7) According to the ISO 10993 standard, after diluting the leaching solution of the pure zinc sample by 10 times and 4 times, conduct a biocompatibility evaluation. When MC3T3 cells are cultured for 1 day, the cell activities are 90% and 22% respectively, as Figure 5 shown. The live-dead staining results are as Figure 6 shown, showing that the cells are spindle-shaped and have filamentous pseudopodia, and the cell state is good, indicating good biocompatibility.

[0062] Example 2

[0063] The operation method of this embodiment is exactly the same as that of Example 1. The only difference is that the sintering temperature is 420 °C. The mechanical property test results of the prepared pure zinc specimens are shown in Table 1, showing certain mechanical characteristics.

[0064] Example 3

[0065] The operation method of this embodiment is exactly the same as that of Example 1. The only difference is that the temperature used during the sintering process is 480 °C. The mechanical property test results of the prepared pure zinc specimens are shown in Table 1.

[0066] Table 1: Comparison of the mechanical property test results of the above three examples with the properties (pure zinc specimens prepared by casting method and hot rolling) recorded in the literature data

[0067]

[0068]

[0069] The microscopic morphology of the pure zinc powder used in Example 1 is as Figure 1 shown. The powder has good sphericity, uniform distribution, there are some satellite powders, good fluidity, and meets the requirements of binder jet printing.

[0070] Figure 2 This is the microscopic structure and element analysis of the pure zinc specimen prepared by binder jetting in Example 1. It can be seen that after sintering, sintering necks are formed between some powder particles, and the structure is dense. The results of energy spectrum analysis show that the O element is enriched at the edges of the particles, and the center of the particles is pure zinc element, and the results show that there is no C element. Since the liquid phase cannot fill all the spaces inside the specimen, some connected and unconnected pores are left in the specimen. At the same time, when designing specimens with certain pores (microchannels), they can also be retained after sintering.

[0071] The stress-strain curve in Example 1 is as Figure 3 shown, indicating that the sample in Example 1 has certain mechanical properties and can meet the requirements of the mechanical properties of bone implants and vascular implants for materials.

[0072] Due to the residual pores during the sintering process, the surface area of the sample in contact with the simulated body fluid increases, accelerating the degradation rate, which is much faster than that of the zinc-based alloy printed by laser powder bed fusion, and is more compatible with the rate of bone regeneration, and is suitable for use in implant positions with higher requirements for the degradation rate. At the same time, the surface of the specimen printed by binder jetting has a hierarchical structure, which does not exist in laser powder bed fusion or other printing methods. This hierarchical structure and pores are also beneficial to cell adhesion and growth, improving the biocompatibility of the zinc-based alloy printed by binder jetting.

[0073] Combined with Table 1 andFigure 4 , Figure 5 , Figure 6 The results show that the medical degradable zinc alloy prepared by the technical solution of the present invention meets the mechanical properties of materials for bone implants and vascular implants, and at the same time has an appropriate degradation rate and good biocompatibility, and it is expected to be further applied to the implantation of orthopedic and vascular stents in clinical practice.

[0074] The above description shows and describes several preferred embodiments of the present invention. However, as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be changed within the scope of the application concept described herein through the above teachings or the technology or knowledge in the relevant field. And any changes and modifications made by those skilled in the art without departing from the spirit and scope of the present invention shall fall within the protection scope of the appended claims of the present invention.

Claims

1. A manufacturing method of a medical degradable zinc-based alloy, characterized in that, The method includes the following steps: S1. Dry the zinc-based alloy powder material and place it in a powder feeder, and select a binder corresponding to the powder material; S2: Lay a layer of the powder material on the substrate of the printing platform. According to the constructed model, selectively spray the binder on the surface of the powder layer formed by the powder material to cure the cross-sectional pattern of the constructed model; Then the printing platform descends by the thickness of a powder layer, and then lay another layer of powder material. Repeat the above process until the constructed model is printed; S3. After printing, remove the entire substrate carrying the printed model and place it in a vacuum oven, keep it warm for a certain time to strengthen the curing strength of the binder. After curing, remove the excess powder to obtain a green body; S4. Debind and sinter the green body to obtain a sintered part of a medical degradable metallic zinc alloy.

2. The method according to claim 1, wherein The particle size of the zinc-based alloy powder material is 5 - 50 μm.

3. The method according to claim 1 or 2, characterized in that The drying temperature in step S1 is: 60 - 100 °C, and the time is 8 - 12 h.

4. The method according to claim 1, characterized in that The laid powder layer is multiple layers, the thickness of each layer is 30 - 50 μm, and the powder laying speed is 30 - 60 pps.

5. The method according to claim 4, wherein A piezoelectric nozzle is used to spray the binder. The saturation of the binder is 60 - 90%, the printing speed of the nozzle in the X-axis is 300 - 500 pps, and the printing speed in the Y-axis is 50 - 150 pps.

6. The method according to claim 1, characterized in that, In S3, a vacuum oven is used for curing. The curing temperature is 150 - 250 °C, and the holding time is 120 - 300 min.

7. The method according to claim 1, wherein The debinding temperature in S4 is 200 - 350 °C, the holding time is 60 - 300 min, and the heating rate is 2 - 5 °C / min.

8. The method according to claim 1, characterized in that, The sintering temperature in S4 is 420 - 480 °C, the holding time is 240 - 500 min, and the heating rate is 1 - 3 °C / min.

9. A medical degradable zinc-based alloy, characterized in that, The alloy is manufactured by the method described in any one of claims 1 - 8. Its surface is a controllable hierarchical porous structure or a dense structure, the compressive strength is 22 - 50 MPa, the hardness is 14 - 42 HV, and the in vitro degradation rate at 28 d is 0.13 - 0.67 mm / year.

10. An application of the medical degradable metallic zinc alloy according to claim 9 in clinical medical implant devices.

Citation Information

Patent Citations

  • Preparation method of room-temperature high-plasticity zinc alloy

    CN110205505A

  • Three-dimensional printing rapid prototyping method

    CN108580891A

  • Method for preparing zinc-magnesium alloy product through 3D gel printing

    CN111761066A

  • Binder for binder injection additive manufacturing of medical porous titanium-based alloy as well as preparation method and application of binder

    CN116218421A

  • Method for printing titanium alloy through binder

    CN116237538A